PENGELOLAAN SAMPAH BERBASIS SUMBER SERTA PRAKTEK PEMBUATAN ECO-ENZYME DAN KOMPOS PADA MASYARAKAT YANG ADA DI DESA BLAHKIUH - Kusumawati, Ni Putu Ayu; Ayu, Putu Cita; Mahayasa, I Gede Aryana; Yuliantari, Ni Putu Yeni (UNHI Press, 2025)
Waste is one of the main problems in some areas, including in Blahkiuh village, source-based waste management offers various solutions by involving the community in managing waste in their respective home environments. This outreach aims to increase community awareness and skills in source-based waste management and the practice of making ecoenzymes and making compost fertilizer. Econzym is a brown liquid with a sour aroma resulting from fermentation of brown sugar or molasses with the addition of fruit, vegetable waste and water in a ratio of 1: 3: 10 which is fermented for 3 months or more. Compost fertilizer is an organic fertilizer produced from the process of decomposing organic materials such as dry leaves, grass, vegetables and other organic waste, water and also provided with fertile soil in a ratio of 3: 1. This community service activity is carried out with the hope of being able to open up people's insight. is in the village of Blahkiuh in order to utilize source-based waste produced from household waste into something useful.